Possible impact of use of a ketogenic diet in pregnancy on the fetus: Review of animal and human studies - Agata Miłosz; Justyna Michalczyk; Iwona Morawik; Klaudia Długoborska; Monika Gesek (NFS Journal)
Balanced diet sufficient in all nutrients is crucial to human development and health, especially for pregnant women, whose diet has a direct impact on the appropriate development of the fetus [1]. In addition, it may lead to epigenetic changes in the fetus that affect the child's health and functioning in adulthood [2]. The ketogenic diet is characterized by increased fat content with reduced carbohydrate supply [3, 4]. It is an effective form of treatment for many diseases including epilepsy, obesity, neurodegenerative diseases and some metabolic disorders.In women with Polycystic Ovary Syndrome ketogenic diet has a positive effect on fertility by reducing weight, insulin resistance and hormonal regulation [4–7]. However, it can contribute to mineral and vitamin deficiencies, hypoproteinemia or the development of hepatic steatosis and kidney stones [4, 8]. Due to the duality of possible effects, the potential benefits of a ketogenic diet in pregnancy should be considered carefully. Moreover, there is a need for more human studies determining the safety of the ketogenic diet for both the fetus and the mother. The purpose of this review is to present recent studies evaluating the effects of maternal use of the ketogenic diet during pregnancy on fetal development and the possible advantages and drawbacks of its use.